2012
DOI: 10.4137/hacce.s10596
|View full text |Cite
|
Sign up to set email alerts
|

Timing, Duration and Quality of Sleep, and Level of Daytime Sleepiness in 1166 Retired Seniors

Abstract: A telephone survey of 1166 community resident seniors (658 male, 508 female, age between 65 and 97 years, mean 74.8 years) was undertaken, which included among other components telephone versions of the Pittsburgh Sleep Quality Index (PSQI), the Epworth Sleepiness Scale (ESS), and the Sleep Timing Questionnaire (STQ). The median PSQI score was 5 and the median ESS score 6, suggesting that neither sleep problems, nor daytime sleepiness problems, were particularly prevalent in this sample of seniors. The STQ ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Table 1 reveals that this sample showed some sleep disruption and a below average sleep efficiency, netting only 6.6 hours of sleep per night, which is close to the 25th percentile value found for 1166 seniors (65y+) in our recent telephone survey study [22]. Because higher scores on the PSQI represent worse sleep, the pattern of correlations (Table 2) was consistent in showing a worsening of sleep with increasing depressive symptoms.…”
Section: Resultssupporting
confidence: 77%
“…Table 1 reveals that this sample showed some sleep disruption and a below average sleep efficiency, netting only 6.6 hours of sleep per night, which is close to the 25th percentile value found for 1166 seniors (65y+) in our recent telephone survey study [22]. Because higher scores on the PSQI represent worse sleep, the pattern of correlations (Table 2) was consistent in showing a worsening of sleep with increasing depressive symptoms.…”
Section: Resultssupporting
confidence: 77%
“…These numbers are important to emphasize that sleep quality should be considered as a complex construct. To properly study this construct, distinct methods, with objective and subjective measures, have been developed ( 39 ). Despite emerging as a gold standard subjective tool for sleep quality estimation, PSQI does not correlate well with polysomnography, possibly because of the need for optimal cognitive function to answer the questionnaire ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason for this is that insomnia in older adults is merely the result of normal ageing and does not necessarily affect daytime functioning 43 . Moreover, older individuals show less compensatory drowsiness after sleep loss than younger individuals and are more tolerant to sleep loss 44 . Notably, this study found that hypnosedative use was associated with a lower likelihood of ESS‐defined daytime sleepiness.…”
Section: Discussionmentioning
confidence: 70%
“…43 Moreover, older individuals show less compensatory drowsiness after sleep loss than younger individuals and are more tolerant to sleep loss. 44 Notably, this study found that hypnosedative use was associated with a lower likelihood of ESSdefined daytime sleepiness. This finding is consistent with a previous study that measured daytime sleepiness using the ESS.…”
Section: Correlates For the Ess And Factors-defined Daytime Sleepinessmentioning
confidence: 62%